Outpatient pain clinic and intranasal fentanyl to improve sickle cell disease outcomes. Issue 10 (15th August 2020) - Myrick, Raven; Blakemore, Shaundra; Waite, Emily; Pernell, Brandi; Madan‐Swain, Avi; Hilliard, Lee; Lebensburger, Jeffrey
Abstract: Background: Acute pain events are a leading complication for sickle cell patients. In an attempt to improve pain outcomes, we developed an outpatient pain clinic, and included intranasal fentanyl in the opioid emergency department (ED) pain order set. We evaluated admission rates and opioid administration for patients that attended both the outpatient pain clinic and ED within a 3‐month period. Methods: We recorded the admission rate, IV morphine equivalents, and time from triage for each opioid order and administration from both an outpatient pain clinic and ED visit within a 3‐month period for an individual pediatric patient with sickle cell disease. Results: Thirty patients received acute pain management in both settings. We identified a significant reduction in hospital admission when patients received care in the pain clinic as compared to the ED (17% vs 43%, P = .02). Additionally, outpatient pain clinic patients received significantly less IV morphine equivalents than patients received in the ED (5.6 vs 10.6 IV morphine equivalents, P < .0001). In the ED, intranasal fentanyl was administered in a significantly shorter time than patients ordered intravenous opioid (43 vs 75 min, P = .02). The mean time to receiving an opioid in the outpatient pain clinic was 57 min. Conclusion: The use of an outpatient pain clinic can reduce admission rates as compared to the ED. The use of intranasal fentanyl reduced the time to first opioid administration in the ED. Patient‐centered research or quality improvement projects should continue to focus on novel approaches to acute pain event management.